David A. Robinson's Modeling the Oculomotor Control System - Robinson, David A. (Progress in brain research, 2022)
"Modelling: The Oculomotor Systems, Volume 269 in the Progress in Brain Research serial highlights new advances in the field with this new volume presenting interesting chapters on topics including The function and phylogeny of eye movements, The behavior of motoneurons, Statics of plant mechanics, Dynamics of plant mechanics, The functional operation of the vestibulo-ocular reflex, Basic framework of the vestibulo-ocular reflex, Oculomotor signals, Signal processing in the vestibulo-ocular reflex, Plasticity and repair of the vestibulo-ocular reflex, The behavior of the optokinetic system, Models of the optokinetic system, Neurophysiology of the optokinetic system, and much more." -- Provided by publisher.